Tate Sensorium: an experiment in multisensory immersive design. (2nd September 2018) - Pursey, Tom; Lomas, David
ABSTRACT: "Tate Sensorium" was a project by creative partnership Flying Object at Tate Britain in 2015 that explored experimentally the scope for enhancing the experience of visual art by the addition of sounds, taste, touch and smell. As discussed by Tom Pursey, co-creator of "Tate Sensorium", four major works were chosen from Tate Britain's collection. Introducing new technologies from the field of virtual reality, "Tate Sensorium" aimed to produce an experience for museum goers that was immersive rather than detached, and that by engaging all the senses (not just vision) was more vivid and more memorable. Lomas's response contextualizes the intervention within the growth of an experience economy, and through a close focus on Francis Bacon's Figure in a Landscape (1945), assesses from an art historical point of view the merits and potential pitfalls of this salutary and timely challenge to Modernism's "pure opticality".